2020
DOI: 10.3389/fpubh.2020.589742
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise, Social Interaction, Access to Care, and Community Service: Mediators in the Relationship Between Socioeconomic Status and Health Among Older Patients With Diabetes

Abstract: The differences in socioeconomic status (SES) will cause a disparity in the health of the elderly. Taking diabetes as an example, previous studies have focused on risk factors of diabetes, while the relationship and mechanism between SES, multi-faceted factors, and the health of older patients with diabetes are not well-understood. This study aims to investigate the association between SES and health in older patients with diabetes and the interrelated mediators between them. Based on the data of the Chinese L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…The Chinese Longitudinal Healthy Longevity Survey (CLHLS) was conducted on a randomly selected sample from half of the counties and cities in 23 of the 31 provinces in China, and is the largest set of survey data on older adults in China, covering about 85 percent of the total population [ 34 , 35 , 36 ]. To date, the CLHLS has conducted face-to-face interviews in 1998, 2000, 2002, 2005, 2008–2009, 2011–2012, 2014, and 2017–2018 using internationally compatible questionnaires conducted in the provinces’ respective native languages.…”
Section: Methodsmentioning
confidence: 99%
“…The Chinese Longitudinal Healthy Longevity Survey (CLHLS) was conducted on a randomly selected sample from half of the counties and cities in 23 of the 31 provinces in China, and is the largest set of survey data on older adults in China, covering about 85 percent of the total population [ 34 , 35 , 36 ]. To date, the CLHLS has conducted face-to-face interviews in 1998, 2000, 2002, 2005, 2008–2009, 2011–2012, 2014, and 2017–2018 using internationally compatible questionnaires conducted in the provinces’ respective native languages.…”
Section: Methodsmentioning
confidence: 99%
“…A large body of literature has focused on the health effects of the physical and social neighborhood environment. Scholars have found that the physical neighborhood environment such as the noises and environmental pollution around residences can reduce residents' self-rated physical and mental health [11][12][13][14][15], while sound public facilities and complete medical services can make residents engage in more physical exercise and get easier access to medical assistance, further lowering the incidence of chronic diseases and improving their self-rated physical and mental health [16][17][18][19][20][21][22]. The influence of the social neighborhood environment on residents' health has also drawn certain research attentions.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that acute hospitalization represented a tipping point for older adults in deprived settings, which may be amplified by lower access to and engagement with community health and social care supports and services. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%